2023
DOI: 10.1021/acs.energyfuels.2c03850
|View full text |Cite
|
Sign up to set email alerts
|

On Fractioning the Tire Pyrolysis Oil in a Pilot-Scale Distillation Plant under Industrially Relevant Conditions

Abstract: Tire pyrolysis oil (TPO) is one of the most interesting products derived from the pyrolysis of end-of-life tires. Among others, it contains valuable chemicals, such as benzene, toluene, ethylbenzene, and xylene (BTEX), as well as limonene. In order to recover these chemicals, a pilot-scale distillation plant has been designed, erected, and operated using TPO derived from an industrial-scale pyrolysis plant. The distillation facility consists of a packed column (20 kg/h) and is within the fifth technological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Alternatively, after being subjected to additional upgrading as hydrotreatment for heteroatoms reduction, they can be co-fed into other refinery units along with petroleum streams to be further treated. The aforementioned conclusions have been also corroborated in an industrially relevant packed distillation column . Two different fractions, namely, light and heavy fractions, were obtained depending on the reboiler temperature (250290 °C) and reflux ratio (up to 2.4).…”
Section: Processing Raw Tire Pyrolysis Oil In Conventional Refineriessupporting
confidence: 58%
See 4 more Smart Citations
“…Alternatively, after being subjected to additional upgrading as hydrotreatment for heteroatoms reduction, they can be co-fed into other refinery units along with petroleum streams to be further treated. The aforementioned conclusions have been also corroborated in an industrially relevant packed distillation column . Two different fractions, namely, light and heavy fractions, were obtained depending on the reboiler temperature (250290 °C) and reflux ratio (up to 2.4).…”
Section: Processing Raw Tire Pyrolysis Oil In Conventional Refineriessupporting
confidence: 58%
“…Results for different TPOs have shown initial and final distillation points between 69 and 150 °C and between 514 and 600 °C, respectively (Figure ). ,, Recently, Martínez et al reported a relatively high distillation temperature at which 50% of TPO evaporates (T 50 ) of 243–350 °C, thus confirming the unrefined nature of raw TPO. The TPO was produced in an industrial-scale pyrolysis plant based on the auger technology using a nonisothermal profile (750–450 °C).…”
Section: Raw Tire Pyrolysis Oilmentioning
confidence: 92%
See 3 more Smart Citations